KALKULATOR DIGITAL DETEKSI DINI PREEKLAMPSIA BAGI BIDAN PUSKESMAS - Fatmah Indriana Fuaida; Nadya Dwita Fatma Sari; Elsy Juni Andri Kariny (Jurnal Medicare, 2026)
Introduction:One of the primary causes of morbidity and mortality in mothers and perinatals is preeclampsia, particularly when the illness develops early in pregnancy. A rapid and substantial increase in body weight during pregnancy is the first immediately detectable symptom of preeclampsia. Because conducting standard pregnancy exams can avoid preeclampsia. Objectives: Development of a digital calculator application for midwives in early prevention of preeclampsia in pregnant women. Method: using the Research and Development (RnD) method. The sampling technique used total sampling with a total sample of 32 midwives. The research was conducted at the Pagelaran Public Health Center in May 2024. The data analysis used TAM (Technology Acceptance Model). Result: According to the evaluation results, 93.5% of respondents felt that the digital calculator application was useful for detecting preeclampsia at an early stage, and 81.12% felt that it was easy to use. This demonstrates how midwives can benefit and find it more convenient to prevent preeclampsia by using a digital calculator application for early identification of preeclampsia. Research conclusion: In order to aid in the early prevention of preeclampsia, midwives could benefit from the creation of a digital calculator application, particularly one that calculates BMI, MAP, and ROT.